2017
DOI: 10.1115/1.4035874
|View full text |Cite
|
Sign up to set email alerts
|

Cloud-Supported Coverage Control for Persistent Surveillance Missions

Abstract: A decomposition-based coverage control scheme is proposed for multi-agent, persistent surveillance missions operating in a communication-constrained, dynamic environment. The proposed approach decouples high-level task assignment from low-level motion planning in a modular framework. Coverage assignments and surveillance parameters are managed by a central base station, and transmitted to mobile agents via unplanned and asynchronous exchanges. Coverage updates promote load balancing, while maintaining geometri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 48 publications
0
2
0
Order By: Relevance
“…In the proposed model, the overall number of UAVs in the surveillance is set as U sys and the UAV is regarded as a resource in the repository pool [34], where the total surveillance capacity is P sys .…”
Section: Problem Formulationmentioning
confidence: 99%
“…In the proposed model, the overall number of UAVs in the surveillance is set as U sys and the UAV is regarded as a resource in the repository pool [34], where the total surveillance capacity is P sys .…”
Section: Problem Formulationmentioning
confidence: 99%
“…Research interest for the coverage and coordination of multi-agent has shown an increase in the field of artificial intelligence (AI) and control [1,2,3,4,5,6]. In particular, coverage control using multiple robots with limited sensing capabilities has received significant attention recently due to its versatility in many applications, such as mapping, patrolling, surveillance, and complete coverage [3,4,5,6,7,8,9,10,11]. However, it is more difficult to achieve persistent coverage for a group of multiple robots considering obstacle avoidance and coverage period, because mission domains may have differently shaped obstacles, as well as more complicated constraints.…”
Section: Introductionmentioning
confidence: 99%